The Development of Assistive Systems to Support Older People: Issues that Affect Success in Practice - Hallewell Haslwanter, Jean; Fitzpatrick, Geraldine (Technologies (Basel), 2018)
Due to an aging population in Europe, the development of Ambient Assisted Living technologies (AAL) is increasingly the target of research financing. These technologies promise to enable older people to remain in their own homes longer, something many people report wanting and which may also reduce the costs of care. To date however there are few systems on the market. Other studies have tried to understand this by looking at user acceptance. However, by looking only at the user acceptance, we may miss important aspects to explain why systems went wrong in the first place, since decisions made during the development may affect the success later. To address this, we report on a study in which we applied qualitative methods, including workshops and an interactive poster, to consult with people who have experience in the development of these technologies. We present the common issues reported across various AAL development projects done in Europe that the participants thought were important to the success or failure of projects. We also describe some ideas from participants for addressing some of these problems. The results demonstrate the importance of issues related to financing with grants for projects but also the need for improved user-centered practice.